(untitled) (Research, Society and Development, 2021)
Scientifically, the death is a biological, natural and inevitable event that characterizes the end of life, being considered the irreversible collapse of the functioning of organs. This study objectified to investigate how the nursing trainee deals with the process of death and mourning. This is a descriptive-exploratory cross-sectional field research, with a qualitative approach, performed in a general hospital and in a maternity hospital located in a municipality in the state of Maranhão. The sample consisted of 10 nursing trainees. As result, it was found that nursing trainees have difficulties dealing with death and mourning. The main feelings awakened against death were impotence, sadness, failure, frustration, pain, anguish, and coldness. So, to protect themselves, the academics create strategies, of which the acceptance, rationalization, religiosity, distancing and negation stand out. It was also realized that their understanding of the finitude of life is related to the personal experiences of each one, however, it was noted that the death of children, young people and cancer patients are the most difficult to deal with. It is concluded, due the mentioned aspects, the importance of introducing disciplines in the curriculum that approaches the process of death / dying and mourning. It is recommended that the nursing trainee search to accomplish classes, post-graduations and specializations during his professional life, in order to obtain knowlegde about how to deal with terminal situations, providing quality assistance and sharing concepts and experiences.